STATE OF ENZYMES OF CAVITY, MEMBRANE DIGESTION. ABSORPTION OF CARBOHYDRATES IN PATIENTS WITH COMPLICATED GASTRODUODENAL ULCERS BLEEDING (World Bulletin of Public Health, 2023)
In parallel with clinical, anamnestic and instrumental studies, to study the functional state of the digestive-transport conveyor of the SI, by simultaneously determining the activity of enzymes involved in cavity, membrane hydrolysis and absorption of carbohydrates in patients with gastroduodenal bleeding (GDB) of varying severity
Keywords: Gastric ulcer; gastroduodenal bleeding; duodenal ulcer